2014
DOI: 10.1186/preaccept-7015597211664438
|View full text |Cite
|
Sign up to set email alerts
|

Distance decay and persistent health care disparities in South Africa

Abstract: BackgroundAccess to health care is a particular concern given the important role of poor access in perpetuating poverty and inequality. South Africa’s apartheid history leaves large racial disparities in access despite post-apartheid health policy to increase the number of health facilities, even in remote rural areas. However, even when health services are provided free of charge, monetary and time costs of travel to a local clinic may pose a significant barrier for vulnerable segments of the population, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Second, some patients incur considerable expenses in travel costs. These costs would be invariably significantly greater for the poorest sections who tend to live farther from health facilities [ 20 ]. A third possibility is informal charges whereby health workers could have sold drugs or received bribes to perform medical tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some patients incur considerable expenses in travel costs. These costs would be invariably significantly greater for the poorest sections who tend to live farther from health facilities [ 20 ]. A third possibility is informal charges whereby health workers could have sold drugs or received bribes to perform medical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, findings in Burkina Faso show that poor quality of available TB treatment resulted in patients incurring cost in the private sector [ 19 ]. A study in South Africa showed that long distance to facilities represented a financial barrier and added a significant portion to the cost of seeking care [ 20 ]. These studies suggest that financial protection is closely related to the quality of the health-care system or the integrity of implementation of free health care policy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was a clear difference in uptake of HIV testing between those who owned cars and those who used public transport, leading to a high contribution to inequality. This result is impressive in that even though the poor rely on public transport and largely live further from health facilities, 34 uptake of HIV testing is better among them. This is a progress worth to note as other countries battle with accessibility to healthcare for their populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that early HIV testing and engagement with antiretroviral therapy (ART) reduces morbidity, mortality, and infectiousness of the virus (Anderson et al 2014; Coetzee et al 2004; Cohen et al 2011; Eaton et al 2014; Mills et al 2011; Smith et al 2013; Wouters et al 2007). Yet, many South Africans do not visit health facilities for regular checkups (McLaren et al 2014). Thus, community-based HTC has become an important strategy adopted by the South African government as it seeks to attain the first 90 target (diagnosing 90% of people with HIV who do not know their HIV status) (South African Department of Health 2015; World Health Organization 2015).…”
Section: Introductionmentioning
confidence: 99%